Tingkat Pendidikan Ibu dan Penggunaan Oralit dan Zinc pada Penanganan Pertama Kasus Diare Anak Usia 1-5 Tahun: Sebuah Studi di Puskesmas Janti Malang - Illahi, Ratna Kurnia; P., Fitra Firnanda; Sidharta, Bambang (Brawijaya University, 2016)
Diarrhea was a condition when a person experienced disturbing bowel movement and soft or liquid stool consistency, three times or more in a day. To this day, diarrhea is one of the major public health problems in developing countries including Indonesia. Mother’s level of education, amongst other things, is likely influencing the treatment choice for children’s diarrhea. The purpose of this study was to determined the influenced of mother’s level of education on the use of oralit (oral rehydration therapy) and zinc in treating diarrhea experienced by children aged 1-5 years old. The sampling technique used was purposive sampling with 100 respondents. The result of the study from chi square analysis gave the p value of 0.528 (p > 0,05), and coefficient correlation of 0.176 (very low). Thus, it can be concluded that the mother’s level of education had no influence on the used of oralit and zinc for the first treatment of diarrhea amongst children aged 1-5 years old.